To Assess the Relationship between Depression and Religious Belief among Medical Students of Larkana - Sohu, Abdul Sami; Muhammad Moazzam; Pirzado, Imran Ali; Khan, Samiya; Deep, Aman; Raza, Hasnain; Siyal, Fahad Jibran (Indus Journal of Bioscience Research, 2024)
Depression is considered as a disorder which involves thoughts, mood and body, Medical colleges environment is considered to be stressful, which leads to negative effects on health, wellness and academic performance. Unfortunately, in Pakistan depression among medial students are being neglected and because of that high proportions of depression is being reported worldwide especially in medical students. The increase in interest has been found recently between mental or physical health and religion and majority of studies have variable like positive health and religion. A Cross Sectional Descriptive study was conducted at SMBBMU Larkana from 1st July 2023 to 30th December 2023 having a sample size of 376 with a validated questionnaire was being used. In this study only those students were selected who were studying at SMBBMU Larkana and all those students who were not enrolled at SMBBMU Larkana were excluded. The data was analyzed with the help of Spearman’s correlation test and the p value was of significance but the association between BDI and religious belief was very weak and statistical significant distribution of data was also found with the help of One-Sample Kolmogorov-Smirnov Test. This study has revealed many important aspect and factors related with mental health and religious life and a positive correlation has been associated with religious belief and depression, but still there is certainty that which part of religious life are most psychological beneficial to whom and why and the future research on health and religion requires a careful consideration between this complex and multifaceted relationship.